Effects of ionic dissolution products from bioactive glass-ceramic scaffolds on the cellular and molecular response of endothelial cells and fibroblasts under hyperglycemia - Haro Durand, Luis Alberto (2019)
Several aspects of tissue repair are altered in diabetes mellitus (DM) i.e., endothelial cells and fibroblasts are affected by cellular dysfunction in a hyperglycemic (HG) environment. Thus, it is of biomedical interest to study different therapeutic strategies to optimize the repair and/or regeneration of tissues under HG conditions.